The speed of corneal epithelial wound healing - Dale, P; Sherratt, J; Maini, P (1994)
We propose a reaction-diffusion model of the mechanisms involved in the healing of corneal surface wounds. The model focuses on the stimulus for increased mitotic and migratory activity, specifically the role of epidermal growth factor. We determine an analytic approximation for the speed of travelling wave solutions of the model and verify the result numerically. The predicted speed compares very well with experimentally measured healing rates.